The meaning of curriculum-related examination standards in Scotland and England: a home-international comparison - Baird, J; Gray, L (Taylor and Francis, 2016)
The ways in which examination standards are conceptualised and operationalised differently across nations has not been given sufficient attention. The international literature on standard-setting has been dominated by the psychometrics tradition. Broader conceptualisations of examination standards have been discussed in the literature in England, which has curriculum-related examinations at the end of schooling. There has, however, been little analysis of conceptualisations of examination standards in Scotland. Different education systems and examinations operate in Scotland and England, and the stated value positions and processes relating to examination standards differ markedly. This paper critically examines policy positions on assessment standards in Scotland and England through the lens of recent theories of standard-setting. By analysing public statements on standards, the paper illuminates similarities and differences in conceptual bases and operational approaches, and examines the effects of these on outcomes for candidates. We conclude that both systems are operationalising attainment-referencing, but with different processes in Scotland and England and these practices do not fit within previous examination standards classifications. As such, the paper moves examination standards theory forward by concluding that there is at least one superordinate definitional category that draws upon more than one definitional stance.